Recovery of the geological landscape as a successful geo-tourism site case study: Gunung Keriang, Kedah / Muhammad Adam Zakaria - Zakaria, Muhammad Adam (2017)
Today, senous degradation of the geo-heritage has lead by technological development, economic and population growth and social changes in most parts of the world. These occurrences have encouraged many researchers and nature-lovers to a greater appreciation of this fragile natural environment and have resulted in numerous and vary studies conducted in order to conserve it. Methodology had been used in this project, (i)lan McHarg's Ecological Inventory Method and (ii)Design development for proposed strategies. This study showed that several key success factors for sustainable conservation which includes the level of the stakeholders' awareness, participation and appreciation towards heritage values and its economic potential and enforcement of legislation or policy will bring toward the successful of the geo-tourisrn. Embracing this fact, and recognizing its implications for the nature, innovative public education programs and promotional activities will discourage the massive quarrying and the disoriented cultural-spatial design on site. Indirectly, the strong genius loci and successful ecosystem can be implemented. Having shown the importance of these geological landscape, the last sections of the study show how the present practice of environmental designers preclude the generation of ideas towards successful geo-tourism in Gunung Keriang, Kedah.